Penggunaan Tudung Saji Insulator untuk Memperpanjang Masa Simpan Produk Es Krim - Nadya Husna; Choirul Amri; Haryono Haryono (Poltekkes Kemenkes Yogyakarta, 2021)
Ice cream is food that can be quickly melted in room temperature. Melting ice cream in open space may prone to be contaminated by dust, as well as nuisance animals. Efforts that can be apllied is to store or place the ice cream in a place that meets the requirements. The purpose of this research was to determine the effect of insulated serving hood on the shelf life of ice cream. The study conducted a quasi experiment with post test with control group design. The results showed that ice cream which were stored in insulated serving hood had shelf life of 48,1 minutes and those which were not, had shorter shelf life, i.e. 25,9 minutes. The difference is statistically significant (p-value <0,001). The use of insulated serving hood with ice cream variation as much as 1, 2, and 3 sticks, also have effect to the shelf life (p-value <0,001). Based on the results, it can be concluded that the insulated serving hood innovation is proven able to extend the shef life of ice cream.